2019
DOI: 10.3389/fpls.2019.00694
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Sensitive qPCR Methodology for Detection of the Olive-Infecting Viruses in Portuguese and Tunisian Orchards

Abstract: Sensitive detection of viruses in olive orchards is actually of main importance since these pathogenic agents cannot be treated, their dissemination is quite easy, and they can have eventual negative effects on olive oil quality. The work presented here describes the development and application of a new SYBR ® Green-based real-time quantitative PCR (qPCR) analysis for specific and reliable quantification of highly spread olive tree viruses: Olive latent virus 1 (OL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In our study, OLYaV was frequent (23.5%) in the tested samples similarly to reports from Lebanon, Italy, Spain, and Tunisia [ 12 , 26 29 ]. On the contrary, in previous surveys conducted in Greece, both in olive orchards [ 5 ] and in a germplasm collection of the Institute of Olive Tree, Subtropical Crops and Viticulture (IOSV) in Chania [ 4 ], its incidence was very low (1.2 and 5%, respectively) and similar to that reported in Albania (2%) from Luigi et al [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, OLYaV was frequent (23.5%) in the tested samples similarly to reports from Lebanon, Italy, Spain, and Tunisia [ 12 , 26 29 ]. On the contrary, in previous surveys conducted in Greece, both in olive orchards [ 5 ] and in a germplasm collection of the Institute of Olive Tree, Subtropical Crops and Viticulture (IOSV) in Chania [ 4 ], its incidence was very low (1.2 and 5%, respectively) and similar to that reported in Albania (2%) from Luigi et al [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…An explanation provided in the previous studies, regarding the low infection rate of OLYaV in Greece, was related to the absence or low populations of the putative psyllid vector ( Euphyllura olivinae ) in Greek olive orchards [ 4 , 5 ]. However, from our study, we conclude that high genetic variability and/or low virus titer, both frequently encountered in OLYaV and in other closteroviruses, could also explain the differences observed [ 12 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 65%
“…Although this virus may be associated with a bright yellow discoloration in olive plants [ 2 , 26 , 30 ], changes in vegetative growth [ 31 ], or woody deformations [ 29 ], no such symptoms were observed. OLYaV appears to be one of the most widespread viruses in olives, with infection rates of up to 63% in Tunisia [ 2 , 24 , 26 , 32 ]. High OLYaV infection rates were also recorded in the germplasm repository of the USDA (National Clonal Germplasm Repository, Davis, California) where 93.8% of the tested varieties, including three Greek varieties, were found to be infected [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“… Jiang et al (2013) measured the viral load of HTNV (Hantaan virus) by using an SYBR Green I-based one-step qRT-PCR technique and observed low viral titres in samples with high Ct values. Campos et al (2019) reported that qRT-PCR based on SYBR Green methodology produced high Ct values in low titres of olive viruses. Similarly, de Freitas-Vanzo et al (2021) used the qRT-PCR to quantify BGMV titre in host plants and found variations in symptom expression and BGMV titre between cultivars and lineages at 10 and 25 pi and the bean cultivar “Tangará” as reported in YLV-14 in this research, had a higher Ct value but showed less symptom severity than the other cultivars.…”
Section: Discussionmentioning
confidence: 99%